ANALISIS SUPERVISI AKADEMIK KEPALA SEKOLAH DI SD NEGERI TLOGOWUNGU 01 PATI - Kartiakningsih, Endang Catur; Sajudin, Muhammad; Hartono, Sumber (Jurnal Studi Islam dan Sosial, 2023)
The purpose of this study was to determine the management of academic supervision, to find out the problems faced by teachers in academic supervision, to find out the follow-up to the results of the academic supervision of the principal at SD Negeri Tlogowungu 01, Pati Regency. The results showed that (1) the management of academic supervision by the principal starts from planning, implementing academic supervision activities, there are two stages of supervision carried out, namely academic supervision of learning devices carried out at the beginning of the school year and academic supervision of the learning process carried out by technical supervision individually with class visits. Evaluation and follow-up supervision in the form of indirect coaching in the form of training and workshops (2) All problems faced by teachers in academic supervision can be resolved by starting a meeting and coaching by the principal. (3) Evaluation of academic supervision at SD Negeri Tlogowungu 01 is carried out by the principal and assisted by senior teachers. The results of the teacher evaluation are used to provide input to the teacher